Knowledge and practices on malaria prevention in two rural communities in Wakiso District, Uganda - Musoke, David; Karani, George; Ssempebwa, John C.; Etajak, Samuel; Guwatudde, David; Musoke, Miph B. (African health sciences, 2015)
Malaria is the leading cause of morbidity and mortality in Uganda particularly among children under 5 years of age. Objectives: The study assessed the knowledge and practices on malaria prevention in 2 rural communities in Wakiso District, Uganda with emphasis on the various prevention methods. Methods: The study was a cross-sectional survey carried out among 376 households using both quantitative and qualitative methods. Log-binomial regression, chi square and Spearman's rank order correlation were used to test for associations. Results: The majority of participants (64.6%) had low knowledge on malaria prevention methods, with untreated mosquito nets (81.7%), mosquito coils (36.9%) and insecticide treated nets (29.6%) being the most known methods. Knowledge on malaria prevention methods was associated with age (χ2 = 32.1; p < 0.01), employment status (χ2 = 18.1; p < 0.01), education (χ2 = 20.3; p = 0.01), income (χ2 = 14.5; p = 0.01) and having heard a malaria message in the previous 12 months (χ2 = 92.3; p < 0.01). Households that had at least one mosquito net were 45.5% and net ownership increased with household income. Only 0.5% of the houses had undergone indoor residual spraying in the previous 12 months, while 2.1% had complete mosquito proofing in windows and ventilators to prevent mosquito entry. Conclusion: There is potential to improve practices on malaria prevention by targeting other methods beyond mosquito nets such as installing proofing in windows and ventilators. The integrated approach to malaria prevention which advocates the use of several malaria prevention methods in a holistic manner should be explored for this purpose.
Keywords: Malaria; Prevention; Knowledge; Practices; Integrated approach; Uganda